"Ever old and ever new, keep me travelling along with you": 21st Century Notae Ecclesiae specifically necessary for churches in southern Africa - Duncan, Graham (HTS teologiese studies, 2011)
The ecumenical marks of the church – unity, holiness, catholicity and apostolicity – have served it well as defining characteristics since the 4th century CE. The Reformation required that they be redefined in a particular context in terms of the soundness of doctrine preached, celebration of the sacraments and the exercise of discipline. In the 21st century these ecumenical marks are still relevant not only within an ecclesiastical context but in society using Koffeman’s quality markers of these marks – conciliarity, integrity, inclusivity and authenticity.